Transformation of Customary Law in the Era of Globalization: Impact on Local Legal Identity - Syamsidar (Leges Privatae, 2024)
This article examines the impact of globalization on customary law in Indonesia, focusing on how global social and economic changes affect local legal identities. Globalization, characterized by intense exchanges of information, culture, and technology, has brought about significant changes in the structure and practice of customary law across communities in the archipelago. This study uses a qualitative approach with a case study method to explore how customary law adapts to the pressures and opportunities posed by globalization. The findings suggest that while globalization can accelerate the modernization and recognition of customary law in national and international legal contexts, it also has the potential to threaten the preservation of traditional values and practices. The article identifies challenges, such as conflicts between customary law and modern law, and impacts on social cohesion and the legitimacy of customary law. Based on this analysis, the article proposes strategies to achieve a balance between the integration of customary law and the preservation of local identity, to ensure that traditional values continue to be respected in an increasingly complex global era.